Pengaruh Motivasi, Kedisiplinan, dan Kompensasi Terhadap Kinerja Karyawan CV. Panca Jaya Garmen Kota Probolinggo - Hermawan, Dedi Joko; Suwarno, Ayu Sefti Yuki Rafindana; Junaidi, Junaidi (Ecobuss, 2024)
This research was conducted at CV. Panca Jaya Garmen Probolinggo City with the aim of knowing the effect of motivation, discipline and compensation on Employee Performance at CV. Panca Jaya Garmen Probolinggo City both partially and simultaneously, and to find out which variable has the dominant influence among the three variables. The type of research used is quantitative. The population in this study is CV. Panca Jaya Garmen Probolinggo City with a total sample size of 52 respondents with the sampling technique is a saturated sample. This research data collection uses questionnaires, interviews and documentation. The data analysis method is done by using the Multiple Linear Regression model. The results of this test indicate that partially Motivation (X1), Discipline (X2) and Compensation (X3) have a positive and significant effect on Employee Performance (Y) at CV. Panca Jaya Garmen Probolinggo City. Keyword: Motivation, Discipline, Compensation, Employee Performance.